Barriers to Management of a Foreign Animal Disease at the Wildlife-Domestic Animal Interface: The Case of Rabbit Hemorrhagic Disease in the United States - Shapiro, Hannah G.; Pienaar, Elizabeth F.; Kohl, Michel T. (Frontiers in Conservation Science, 2022)
The increasing global emergence of pathogens transmitted between wildlife and domestic animals are critically important conservation and economic concerns. International organizations, such as the World Organization for Animal Health (OIE), have called for cross-jurisdictional government investment in defensible, reliable surveillance systems and biosecurity measures to prevent pathogen transmission at the wildlife-domestic animal interface. A classic example of a pathogen that transmits across the wildlife-domestic animal interface is rabbit hemorrhagic disease virus 2 (RHDV2), which has spread to five continents in the 11 years since its discovery. RHDV2 is a highly contagious virus that infects wild and domestic rabbits and hares (lagomorphs). Globally, RHDV2 has resulted in population declines of wild lagomorphs, with associated biodiversity and hunting impacts, as well as economic losses for commercial rabbit industries. To assess the degree to which government agencies are positioned to engage in cross-jurisdictional approaches to mitigate pathogen spillover, we conducted the first study of how agricultural and wildlife agencies in the United States of America (U.S.) have responded to RHDV2 since it was detected in wild and domestic lagomorphs in March 2020. We surveyed and interviewed animal health personnel at 95 state wildlife and agricultural agencies, thereby accounting for all 50 states. Agencies have primarily responded to RHDV2 through disease investigations of potential RHDV2 cases, vaccinations, and education and outreach with the public and stakeholder groups. However, agencies’ inconsistent jurisdiction within and across states over lagomorph populations and industries, limited knowledge of wildlife lagomorph populations and the composition of the domestic rabbit industry, and resource constraints have hindered management efforts. Improved understanding of the domestic lagomorph trade and transport routes is urgently needed to mitigate the risks associated with human-mediated movement of rabbits and RHDV2 across the U.S. Greater flexibility in agency funding and increased allocation of discretionary funds to agencies for management of animal diseases would allow agencies to respond more rapidly and effectively to emerging pathogens such as RHDV2. Federal leadership is needed to engage state agencies in collaborative, proactive interagency disease management across the U.S.